Recursos online e software para ensinar e aprender Latim - Balalaieva, Olena (Texto Livre, 2019)
ABSTRACT: The aim of this article is to review electronic resources in Latin, analyzing their didactic potential to help Classical teachers to effectively organize the educational process, diversifying the set of tools, and enhancing their work. Today, most of the useful links are accumulated on domestic professional sites devoted to the study of Latin. Many foreign scientists and teachers simply do not know about their existence. From time to time, attempts are made to summarize information and provide content for studying Classic languages in scientific publications, but such information quickly becomes outdated and needs to be regularly updated. This article provides an overview of the current most popular resources on Latin: digital libraries and databases, online courses, electronic textbooks, dictionary, translators etc.; describing the current state of the development of e-learning tools and websites for the study of Latin in Ukraine.KEYWORDS: electronic educational resources; online resources; language learning; Latin language. RESUMO: O objetivo do artigo é revisar recursos eletrônicos em Latim, analisando seu potencial didático para ajudar os professores clássicos a organizar efetivamente o processo educacional, diversificando o conjunto de ferramentas e aprimorando o seu trabalho. Hoje, a maioria dos links úteis é acumulada em vários sites domésticos dedicados ao estudo do Latim. Muitos cientistas e professores estrangeiros simplesmente não sabem sobre sua existência. De tempos em tempos, são feitas tentativas de resumir informações e fornecer conteúdo para o estudo de línguas clássicas em publicações científicas, mas essas informações rapidamente ficam desatualizadas e precisam ser atualizadas regularmente. Este artigo fornece uma visão geral dos recursos mais populares da atualidade em Latim: bibliotecas digitais e bancos de dados, cursos online, livros eletrônicos, dicionário, tradutores etc.; descreve o estado atual de desenvolvimento das ferramentas de e-learning e sites para o estudo do Latim na Ucrânia.PALAVRAS-CHAVE: recursos educacionais eletrônicos; recursos online; aprendizagem de línguas; língua latina.